Competence as Intervening on Training and Discipline on Student Performance as a Provision for Readiness to Compete in Era 4.0 - Hustia, Anggreany; Sudarta, Sudarta; Rahmawati, Desy (Universitas Indo Global Mandiri, 2025)
The competition in the business world requires companies to recruit human resources with high competence in order to achieve company goals. This study was conducted to determine how the direct and indirect effects of training and discipline on student performance as a provision for readiness to compete in the industrial 4.0 era job market with student competence as an intervening variable. With the aim of providing empirical evidence to prospective graduates, graduate users and parties involved in the world of education. With the results of this study, especially universities can provide strategic policies to prepare prospective graduates to be ready to work by having good abilities and achievements and preparing graduates who are able to compete or compete in the job market in the industrial era 4.0. This study used a questionnaire distributed to 97 students from various universities in Palembang city, South Sumatra.. Students as respondents come from universities in South Sumatra who have participated in training activities both within the university and outside the university environment. The analysis used smartPLS 3.0. The results showed that discipline has a significant effect on student performance; training has a significant effect on competence; and discipline has a significant effect on competence. The results showed that the competency variable had no role for the training and discipline variables on student performance. Further research needs to sharpen indicators and linkages with other variables besides those currently studied. Keywords: Discipline, Competence, Student Performance, Training